Molecular Docking Study: Application to the Epidermal Growth Factor Receptor - Faiza Asli; Imane Bensahbane (Chemistry Proceedings)
With the development of computer tools over the past 20 years, molecular modeling, and more precisely molecular docking (molecular docking), has very quickly entered the field of pharmaceutical research. Our work consists of studying the inhibition of the enzyme EGFR (1M17) involved in cancer with deferent inhibitors derived from quinazoline and quinoline by molecular docking. Ligands L_1 and L_2 are the best ligands for inhibiting the activity of 1M17 since they form a stable complex with this enzyme by better binding to the active site. The results obtained show that ligands L1 and L2 have weak interactions with the active site residue EGFR (1M17), which stabilize the complexes formed with these ligands, allow better binding at the level of the active site, and give an RMSD of L_1 [1.9563 Å] and of L_2 [1.2483 Å]. All the newly designed compounds passed the pharmacokinetic analysis (ADME–TOX) (adsorption, distribution, metabolism, excretion, and other physicochemical tests), passed the drug-likeness test, and also adhered to the Lipinski rule of five.